Comparison between two maintenance feeding regimens after successful cow's milk oral desensitization. Issue 4 (21st May 2013) - Pajno, Giovanni B.; Caminiti, Lucia; Salzano, Giuseppina; Crisafulli, Giuseppe; Aversa, Tommaso; Messina, Maria Francesca; Wasniewska, Malgorzata; Passalacqua, Giovanni
Abstract Background Cow's milk allergy is common in infancy, and total avoidance of this food is the only effective approach. In alternative, oral immunotherapy has been proposed to achieve tolerance. Once desensitization is achieved, daily intake of milk is recommended to maintain it, but this may be impractical for children/parents. We assessed whether a twice weekly maintenance regimen is effective. Methods Children who were successfully desensitized with oral immunotherapy were randomized to two maintenance regimens for 1 year: group A had to eat 150–200 ml milk daily, group B had to eat 150–200 ml milk twice weekly. Both regimens were associated to a totally free diet. Maintenance of tolerance and adverse events were recorded during 1 year. Specific IgE, IgG4 and prick‐by‐prick test to milk were carried out before immunotherapy (T0), before maintenance (T1), and after 1 year (T2). Results Recorded episodes included asthma, oral itching, urticaria, rhinitis, abdominal pain variously combined, usually associated with concomitant illness or exercise. The episodes were 8 in group A and 9 in group B, with no difference. None of the children discontinued the feeding maintenance. Specific IgG4 increased at T1 and remained high at T2. Specific IgE and skin reactivity significantly decreased at T2. There was no difference in those parameters between the groups. Conclusion After achieving desensitization to cow milk with oral immunotherapy, a maintenance regimen with milk given twice weekly is as effective as the daily maintenance.